Proposed Marketing Strategy For N219 Aircraft in Domestic Market (The Indonesian Journal of Business Administration, 2021)
In the last 5 years, the sales of the military aircraft of PTDI has been stagnant. The dependency of PTDI to the military customers’ budget makes the business more volatile and uncertain since it is strongly influenced by political situation and economy changes.To compensate the demand uncertainty from the military market, PTDI has to start expanding its aircraft business to the commercial market. Therefore the N219 aircraft was initiated and PTDI started its development in 2014 and accepted its Type Certification in December 2020. However, despite all the marketing effort since 2018 and high potential market, N219 has not been able to win any contracts from the potential customers in domestic market.This research is using internal and external analysis approach to understand the situation that has been faced by N219. AHP method is also used to understand the criteria and sub criteria that are prioritized by the airlines potential customers to make a decision on buying a new aircraft. The analysis then formulated into SWOT analysis. From it, the author can identify the root causes of N219 business issue.The current Marketing Strategy, Marketing Tactics and also Man power are the main root causes that was identified from the analysis the author had conducted. Therefore, there are several things in those areas that require major changes and are also very crucial, namely Target Market, Positioning, 4P and People plus the Organization.The target market of N219 has to be adjusted with the capability of N219-100. While the new positioning needs to highlight the N219 benefits aside from its product performance. The Marketing Mix stage has to start from strengthening the man power of N219 marketing and sales department and as the consequences, the organization of PTDI should be changed. For the Product aspect, N219 has to offer other value added package to the potential customers, both airlines and local government, such as benefits non-product, namely excellent after sales service, financing facility, long-term pioneer routes flight contract, operation package, human resource development and multiyear budget package. As for the Price aspect, N219 should offer the competitive number for the launching price, while still giving the value added package to the potential customer. Meanwhile, for the Place aspect, PTDI has to consider the expansion of N219 service facility in several areas in Indonesia to provide faster response for the customers. Other than that N219 has to optimize the Digital Platform to increase its accessibility. Last but not least, the Promotion aspect, with an integrated marketing communication approach that is maximizing every marketing channel including Events and Experience, Public Relation and Publicity, Direct Marketing, Interactive Marketing and Personal Selling.The implementation of the Marketing Mix is the responsibility of all parties involved in the company. However, in order to implement the Marketing Mix optimally, the commitment from the management is the first key activity to start focusing on the N219 business. The implementation plan has to be realized within a year since N219 needs to enter the domestic market before it loses its moment and more competitors enter the market. Keywords: N219, marketing strategy, marketing tactics, benefits non-product